Determining The Design Wind Speeds for Building Coastal Structures (Case Study Tartous City) - اسماعيل, لبنى; محمد علاء الدين, (Latakia University Journal -Engineering Sciences Series, 2024)
Studying wind speed and its properties (speed-direction) is one of the most important considerations when designing the costal projects because of the direct relationship between a wind speed and a wave height as well as the importance on gettability wind power in electricity generating. In this research hourly wind speed data and its direction that measured in Tartous meteorological station for 10 years are analyzed statistically by using Excel. This study aimed to estimate wind speed at different return periods in Tartous city by using Weibull probability density function. The parameters of the Weibull distribution (k shape parameter- c scale parameter) are used for finding the wind speed at different return periods; These parameters are estimated by using three methods (maximum likelihood method-moment method-emprical method). These methods results have been compared with the provided data to find their accuracy based on root mean square errors (RMSE), the results showed that the best method of estimation was the maximum likelihood method. The maximum Likelihood method showed that the maximum wind speed for 100 year return period is expected to be of the order of 25.3m/sec and 24.5 m/s from S and SW directions respectively